Injectable thermosensitive hydrogel loading erythropoietin and FK506 alleviates gingival inflammation and promotes periodontal tissue regeneration - Gu, Zhongyi; Qiu, Caiqing; Chen, Ling; Wang, Xiaoli (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Periodontitis is a chronic multifactorial inflammatory disease associated with dysbiotic plaque biofilms and characterized by progressive destruction of the tooth-supporting apparatus. Therefore, there is significant potential in the discovery of drugs that inhibit periodontal inflammatory responses and promote periodontal regeneration.In this study, we generated a periodontitis rat model to detect the effects of chitosan/β-sodium glycerophosphate (β-GP)/glycolic acid (GA) hydrogel carried Erythropoietin and FK506 (EPO-FK506-CS/β-GP/GA). A total of forty-eight male Wistar rats were used to establish the periodontitis model. Drug injection was administered every three days for a total of five times over a two-week period. After a period of two weeks following implantation, the rats underwent anesthesia, and a section of their maxillae encompassing the maxillary first and second molars, along with the alveolar bone, was obtained. micro-CT scanning, histopathology, immunohistochemistry and reverse transcription-quantitative PCR (RT-qPCR) assays were performed. Meanwhile, ELISA assay was performed to detect the levels of inflammatory mediators (TNF-α, IL-6 and IL-1β). observed through micro-CT analysis, when compared to the Model group. EPO-FK506-CS/β-GP/GA hydrogel exhibited notable efficacy in modulating inflammatory mediators . Furthermore, the osteoinductive properties of the EPO-FK506-CS/β-GP/GA hydrogel were extensive, as evidenced by a significant upregulation in the expression of key markers (Collagen I, Runx2, OPN, and OCN) associated with osteoblastic differentiation.Conclusions: Taken together, EPO-FK506-CS/β-GP/GA hydrogel alleviates gingival inflammation and promotes periodontal tissue regeneration in the periodontitis.